Risk factors for acute kidney injury after liver transplantation in intensive care unit: a retrospective cohort study - Neves, Ana Paula Camargos de Figueirêdo; Gomes, Angélica Gomides dos Reis; Vassallo, Paula Frizera; Silva, Ana Cristina Simões e; Penna, Francisco Guilherme Cancela e; Bastos, Fabrício de Lima; Muniz, Mateus Rocha; Rocha, Guilherme Carvalho; Santos Júnior, Augusto Cesar Soares dos; Ravetti, Cecilia Gómez; Nobre, Vandack (São Paulo Medical Journal, 2022)
BACKGROUND: Acute kidney injury (AKI) is a frequent complication during the postoperative period following liver transplantation. Occurrence of AKI in intensive care unit (ICU) patients is associated with increased mortality and higher costs. OBJECTIVE: To evaluate occurrences of moderate or severe AKI among patients admitted to the ICU after liver transplantation and investigate characteristics associated with this complication. DESIGN AND SETTING: Single-center retrospective cohort study in a public hospital, Belo Horizonte, Brazil. METHODS: Forty-nine patients admitted to the ICU between January 2015 and April 2017 were included. AKI was defined from a modified Kidney Disease Improving Global Outcomes (KDIGO) score (i.e. based exclusively on serum creatinine levels). RESULTS: Eighteen patients (36.7%) developed AKI KDIGO 2 or 3; mostly KDIGO 3 (16 out of the 18 patients). Lactate level within the first six hours after ICU admission (odds ratio, OR: 1.3; 95% confidence interval, CI: 1.021-1.717; P = 0.034) and blood transfusion requirement within the first week following transplantation (OR: 8.4; 95% CI: 1.687-41.824; P = 0.009) were independently associated with development of AKI. Patients with AKI KDIGO 2 or 3 underwent more renal replacement therapy (72.2% versus 3.2%; P < 0.01), had longer hospital stay (20 days versus 15 days; P = 0.001), higher in-hospital mortality (44.4% versus 6.5%; P < 0.01) and higher mortality rate after one year (44.4% versus 9.7%; P = 0.01). CONCLUSION: Need for blood transfusion during ICU stay and hyperlactatemia within the first six postoperative hours after liver transplantation are independently associated with moderate or severe AKI. Developing AKI is apparently associated with poor outcomes.